Cinética de sinterização para sistemas à base de SnO2 por taxa de aquecimento constante - Tebcheran, S. M. [UNESP]; Varela, J. A. [UNESP]; Brankovic, Z. [UNESP]; Brankovic, G. [UNESP]; Spagnol, P. D. [UNESP]; Cilense, M. [UNESP]; Perazolli, L. [UNESP]; Longo, E. (Associação Brasileira de Cerâmica, 2003)
Dense tin oxide based ceramics are very promising for technological applications such as varistors and crucibles for melting very corrosive glasses. Several additives have been used in small concentrations as densifying aids for this oxide. In the present study the sintering kinetics of tin oxide was studied considering the effect of sintering atmosphere and of the MnO2 concentration. SnO2-MnO2 systems were prepared from the polymeric precursors method and the obtained powders were characterized by surface area by the BET method. SnO2 powders with varied MnO2 concentrations were pressed in cylindrical shape, and sintered in a dilatometer furnace with constant heating rate and controlled atmospheres. Sintered samples were characterized by scanning electron microscopy. The influence of atmosphere (argon, air or CO2) as well as of the MnO2 concentrations on the sintering kinetics was determined. The kinetics data of linear shrinkage were analyzed in terms of kinetic models for the initial stage of sintering (Woolfrey and Bannister) as well as for the global sintering (Su e Johnson) allowing the determination of the apparent activation energy. Following the determination of the master sintering curve the apparent activation energy of all sintering process were determined as well as its dependence with the atmosphere and manganese concentrations. Based on these values and on the n exponent, determined by the classical grain growth equation, it was concluded that the most probable sintering mechanism is grain boundary diffusion with surface redistribution controlling the kinetics.

Cerâmicas densas de óxido de estanho são muito promissoras para aplicações tecnológicas como varistores e cadinhos de fusão de vidros corrosivos. Vários aditivos em pequenas concentrações podem ser usados como promotores de densificação desta cerâmica. No presente trabalho foram estudadas as cinéticas de sinterização do óxido de estanho, considerando o efeito de atmosfera de sinterização e da concentração de MnO2. Sistemas de SnO2-MnO2 foram preparados pelo método dos precursores poliméricos e os pós obtidos foram caracterizados por medidas de área de superfície específica (BET) e por difração de raios X. Pós de SnO2 com concentrações variadas de MnO2 foram compactados de forma cilíndrica e sinterizados em dilatômetro com taxa de aquecimento constante e atmosferas controladas. Amostras sinterizadas foram caracterizadas por microscopia eletrônica de varredura. A influência da atmosfera (argônio, ar ou CO2) como também das concentrações de MnO2 na cinética de sinterização foram determinadas. Os dados cinéticos da retração linear foram analisados pelos modelos cinéticos para a fase inicial de sinterização (Woolfrey e Bannister) como também para a sinterização global (Su e Johnson) permitindo determinar a energia de ativação aparente. De acordo com a determinação da curva mestre de sinterização, a energia de ativação aparente de todo o processo de sinterização foi determinada bem como sua dependência com a atmosfera e concentrações de manganês. Baseado nestes valores e no expoente n, pode-se determinar, pela equação clássica de crescimento de grão, que o mecanismo de sinterização mais provável é de difusão por contorno de grão com redistribuição superficial controlando a cinética de sinterização.
Sintering kinetics for SnO2-based systems by constant heating rate
Keywords: tin oxide; sintering; sintering kinetics; óxido de estanho; sinterização; cinética de sinterização